Moral Messages and Educational Values In The Film Jumbo - Laidy Simamora (Universitas Hasanuddin, 2026)
This study to analyze the moral messages and educational values in film Jumbo. Literature serves as a medium for conveying ideas, experiences, and values that can influence audiences positively. Film not only functions as entertainment but also as a means of education and character development. This research employs a descriptive qualitative method through literature review. The findings reveal that the film contains various moral messages, including self-confidence and self-acceptance, the importance of avoiding bullying, friendship, courage in facing challenges, and family affection. These values are reflected through the experiences of the main character, Don, who struggles against social stigma and learns to develop confidence with the support of his family and friends. The film also emphasizes educational values related to character building, empathy, perseverance, and respect for others. Jumbo can be regarded as an educational film that provides positive lessons and contributes to the moral development of audiences, particularly children.